Dangerous liaisons at the virological synapse. - Piguet, V; Sattentau, Q (2004)
Cell-to-cell viral transmission facilitates the propagation of HIV-1 and human T cell leukemia virus type 1. Mechanisms of cell-to-cell transmission by retroviruses were not well understood until the recent description of virological synapses (VSs). VSs function as specialized sites of immune cell-to-cell contact that direct virus infection. Deciphering the molecular mechanisms of VS formation provides a fascinating insight into how pathogens subvert immune cell communication programs and achieve viral spread.